COMPARISON OF PRIMARY AND SECONDARY FORMS OF MULTIPLE EVANESCENT WHITE DOT SYNDROME. Issue 12 (December 2022) - Serrar, Yasmine; Cahuzac, Armelle; Gascon, Pierre; Langlois-Jacques, Carole; MAUGET-FAŸSSE, Martine; Wolff, Benjamin; Sève, Pascal; Kodjikian, Laurent; Mathis, Thibaud
Abstract : This study reviewed 101 eyes with multiple evanescent white dot syndrome, including 60 primary and 41 secondary forms of multiple evanescent white dot syndrome triggered by an underlying pathology. Outer retinal lesions on late-phase indocyanine green angiography were less extensive and less symmetrical on the posterior pole in secondary forms of multiple evanescent white dot syndrome. Abstract : Purpose: The aim of this study was to compare primary versus secondary forms of multiple evanescent white dot syndrome (MEWDS) at T0 (baseline) and T1 (1–4 months after the onset of symptoms). Methods: A total of 101 eyes in 100 patients were included in a multicentric retrospective study. Results: Secondary MEWDS was defined as MEWDS associated with underlying chorioretinal inflammatory pathologies, mainly multifocal choroiditis and punctuate inner choroidopathy. Patients with secondary MEWDS were older ( P = 0.011). The proportion of women ( P = 0.8), spherical equivalent ( P = 0.3), and best-corrected visual acuity at T0 ( P = 0.2) were not significantly different between the two groups. The area of MEWDS lesions on late-phase indocyanine green angiography was significantly smaller in secondary MEWDS ( P = 0.001) and less symmetrical with respect to both horizontal ( P = 0.003) and vertical ( P = 0.004) axis. At T0, neither the clinical ( P = 0.5) nor the multimodal imaging ( P = 0.2) inflammation scores were significantly different between the groups. At T1, the multimodal imaging inflammation score was higher in secondary MEWDS ( P = 0.021). Conclusion: In secondary MEWDS, outer retinal lesions are less extensive and located close to preexisting chorioretinal lesions. Mild signs of intraocular inflammation on multimodal imaging are more frequent in secondary MEWDS during recovery. These findings suggest that chorioretinal inflammation may trigger secondary MEWDS.